KNOWLEDGE OF YOUTH WHO JOIN IN PIK-R ABOUT STUNTING AT SMKN 1 POGALAN, TRENGGALEK REGENCY - Elsa upay Malinda; Sri Mugianti; Mujito (Universitas Islam Balitar, 2022)
Stunting is a condition of failure to develop children in the first 1000 days of life. Adolescent knowledge about stunting must be owned by teenagers as successors who will become parents as a provision to prevent stunting. This study aims to determine the knowledge of adolescents who are members of PIK-R about stunting at SMKN 1 Pogalan, Trenggalek Regency. The method used is descriptive quantitative with a population of 82 respondents, the sampling technique used is the total population. The data collection tool uses a questionnaire. The results of the study obtained that the knowledge of adolescents about stunting was 2.5% in the good category, 63.5% in the sufficient category and 34% in the poor category. It was concluded that adolescents who were members of PIK-R did not yet have adequate knowledge about stunting concepts. Health workers are expected to arrange regular education programs at SMKN 1 Pogalan so that teenagers in schools can play a role in accelerating stunting reduction.